The Malaysian generational elderly-friendly housing design features framework (MGens-ElderLyHD) / Dr. Hafiszah Ismail, Dr. Robiah Abd Rashid and Muhamad Saiful Alizan Nordin - Ismail, Hafiszah; Abd Rashid, Robiah; Nordin, Muhamad Saiful Alizan (College of Built Environment, 2023)
The continuous growth of the elderly population in Malaysia will render the country an aging nation status by the year 2030. The elderly population would escalate up to 15 percent out of the overall population in Malaysia.